2015
DOI: 10.1007/s11682-015-9453-x
|View full text |Cite
|
Sign up to set email alerts
|

Go/No Go task performance predicts cortical thickness in the caudal inferior frontal gyrus in young adults with and without ADHD

Abstract: Response inhibition deficits are widely believed to be at the core of Attention-Deficit Hyperactivity Disorder (ADHD). Several studies have examined neural architectural correlates of ADHD, but research directly examining structural correlates of response inhibition is lacking. Here we examine the relationship between response inhibition as measured by a Go/No Go task, and cortical surface area and thickness of the caudal inferior frontal gyrus (cIFG), a region implicated in functional imaging studies of respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 75 publications
3
33
1
Order By: Relevance
“…Prior to analyzing the primary aims, we confirmed that MRI site did not significantly predict subcortical volumes or cortical thickness (p’s>.10); this is consistent with other multi-site MRI studies demonstrating low between-scanner variability in cortical thickness (Han et al, 2006; Dewey et al, 2010; Jovicich et al, 2006) as well as a previous analysis utilizing the current sample (Newman et al, 2015). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Prior to analyzing the primary aims, we confirmed that MRI site did not significantly predict subcortical volumes or cortical thickness (p’s>.10); this is consistent with other multi-site MRI studies demonstrating low between-scanner variability in cortical thickness (Han et al, 2006; Dewey et al, 2010; Jovicich et al, 2006) as well as a previous analysis utilizing the current sample (Newman et al, 2015). …”
Section: Resultssupporting
confidence: 87%
“…Multimodal Treatment Study of Children with ADHD," 1999). For the current neuroimaging study, participants were brought in for an MRI and neuropsychological evaluation at one of six sites (Newman et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…As an additional example of a study employing multiple units of analysis to explore a Cognitive System, Newman et al (2016) focused on the Response Selection construct by examining the relationship between cortical thickness and performance on a go/no-go task. In a sample of 114 adults, 46% of which exhibited symptoms of Attention Deficit Hyperactivity Disorder (ADHD) persisting into adulthood, thickness of the caudal inferior frontal gyrus was associated with poorer response inhibition (i.e., more commission errors) regardless of ADHD symptoms or history of substance abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Regional differences in cortical morphology during development (relative to global brain measures) have been previously linked to different aspects of cognitive function [19][20][21][22][23] . However, previous studies have been underpowered, and did not employ multivariate tools, to assess the contribution of the whole configuration of cortical morphology to individual differences in cognition.…”
Section: Introductionmentioning
confidence: 99%